The definition of immigrant status matters: impact of nationality, country of origin, and length of stay in host country on mortality estimates - Luis Andrés Gimeno-Feliu; Amaia Calderón-Larrañaga; Esperanza Díaz; Clara Laguna-Berna; Beatriz Poblador-Plou; Carlos Coscollar-Santaliestra; Alexandra Prados-Torres (BMC, 2019)
Abstract Background Mortality is a robust indicator of health and offers valuable insight into the health of immigrants. However, mortality estimates can vary significantly depending on the manner in which immigrant status is defined. Here, we assess the impact of nationality, country of origin, and length of stay in the host country on mortality estimates in an immigrant population in Aragón, Spain. Methods Cross-sectional retrospective study of all adult subjects from the EpiChron Cohort in 2011 (n = 1,102,544), of whom 146,100 were foreign-born (i.e., according to place of birth) and 127,213 were non-nationals (i.e., according to nationality). Directly standardized death proportions between years 2012-2015 were calculated, taking into account the age distribution of the European population in 2013. Binary logistic regression was used to compare the four-year probability of death. Results The age- and sex-standardized number of deaths per 1000 subjects were 45.1 (95%CI 44.7-45.2) for the Spanish-born population, 29.3 (95%CI 26.7-32.1) for the foreign-born population, and 18.4 (95%CI 15.6-21.6) for non-Spanish nationals. Compared with the Spanish-born population, the age- and sex-adjusted likelihood of dying was equally reduced in the foreign-born and non-national populations (OR 0.6; 95%CI 0.5-0.7) when the length of stay was less than 10 years. No significant differences in mortality estimates were detected when the length of stay was over 10 years. Conclusions Mortality estimates in immigrant populations were lower than those of the native Spanish population, regardless of the criteria applied. However, the proportion of deaths was lower when immigrant status was defined using nationality instead of country of birth. Age- and sex-standardized death proportions tended to increase with increased length of stay in the host country.